Weidingkapasiteitstudies op veld in die Noord-Kaap - Venter, Izak Stephanus (University of the Free State, 1990)
No abstract available.
Dissertation (M.Sc.Agric. (Animal, Wildlife and Grassland Sciences))--University of the Free State, 1991
Keywords: Pastures -- South Africa -- Northern Cape